ANALISIS SELISIH KURS TRANSAKSI MATA UANG ASING DITENGAH FLUKTUASI EKONOMI PADA PT PERTAMINA (PERSERO) TAHUN 2018-2023 - Hasnawati, Pebriani; Cempaka, Putri; Aziza Arofani, Syofiatul; Rizki, Novia (Universitas Prof.Hazairin,SH Bengkulu, 2024)
In recent years, uncertainty and fluctuations in the global economy, triggered by the Covid-19 pandemic, have posed significant challenges for companies, including PT Pertamina (Persero). One key issue is the volatility in exchange rates between the US dollar and the rupiah, which directly impacts cash flow and profitability, especially in Pertamina’s international transactions. Since the company uses the US dollar as its functional currency, sudden exchange rate changes can increase raw material costs and reduce revenues from products sold. This study aims to examine how PT Pertamina (Persero) handles foreign exchange differences in foreign currency transactions and manages the associated risks to minimize negative effects on its financial statements. The research employs a descriptive quantitative method to explain and describe the company's financial condition in relation to foreign exchange risk. Secondary data from PT Pertamina’s Annual Financial Statements from 2018-2023 is used, including information on foreign currency transactions, exchange rate differences, and the impact of global economic fluctuations. Data analysis is conducted descriptively and qualitatively, involving data collection, classification, and interpretation to assess the effect of economic fluctuations on exchange rates.The findings reveal that exchange rate fluctuations, especially between the US dollar and rupiah, significantly affected Pertamina’s financial performance between 2018 and 2023. While the company recorded its highest profit in 2019 and its largest loss in 2022, the study highlights the importance of hedging strategies to manage exchange rate risks and ensure financial stability.